ANALISIS KINERJA PENGOLAHAN AIR LIMBAH PAVILYUN KARTIKA RSPAD GATOT SOEBROTO JAKARTA - Sumiyati, Sri; Imaniar, Imaniar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Hospitals  produce  solid  waste  and  also  wastewater,  hazardous  and  non-hazardous.  Pavilyun Kartika as a part of RSPAD Gatot Soebroto, produces wastewater that has characteristic like a domestic wastewater. The hazardous waste that produced by Pavilyun Kartika were managed by RSPAD Gatot Soebroto. In Pavilyun Kartika, wastewater with flows 52 m3/days comes from bathrooms  for  patients, laundry,  public  bathrooms,  and  also  kitchen.  Wastewater  of  Pavilyun Kartika contains high BOD, COD, and also Ammoniac, though still in save numbers, because still  under  the  standard  regulation  for wastewater  in  Jakarta.  Wastewater  treatment  plant  in Pavilyun Kartika use extended aeration method, as part of  biological treatment. The principal of the treatment are aeration, sedimentation, and chlorination.